2004
DOI: 10.1182/blood-2003-09-3131
|View full text |Cite
|
Sign up to set email alerts
|

Role of p300 and PCAF in regulating cyclooxygenase-2 promoter activation by inflammatory mediators

Abstract: Coactivators p300 and CREB (cyclic adenosine monophosphate [cAMP]–response element binding protein)–binding protein (CBP) serve as an integrator for gene transcription. Their relative involvement in regulating cyclooxygenase-2 (COX-2) promoter activity had not been characterized. Using fibroblast and macrophage COX-2 transcription as a model, we determined p300 and CBP levels in nuclear extracts and their binding to a COX-2 promoter probe. CBP level was barely detectable and there was little CBP binding. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
114
1
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(128 citation statements)
references
References 34 publications
(42 reference statements)
10
114
1
3
Order By: Relevance
“…In addition, they possess intrinsic histone acetyltransferase (HAT) activity (Shikama et al, 1997). The functional roles of p300 in regulating COX-2 promoter activation have been demonstrated in previous studies of upregulation of COX-2 expression by inflammatory mediators such as phorbol 12-myristate 13-acetate, IL-1b or lipopolysaccharide (Deng et al, 2004). In the case of STAT6, we speculate that p300 may function as a result of its HAT activity and/or by bridging active interaction between STAT6 and general transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they possess intrinsic histone acetyltransferase (HAT) activity (Shikama et al, 1997). The functional roles of p300 in regulating COX-2 promoter activation have been demonstrated in previous studies of upregulation of COX-2 expression by inflammatory mediators such as phorbol 12-myristate 13-acetate, IL-1b or lipopolysaccharide (Deng et al, 2004). In the case of STAT6, we speculate that p300 may function as a result of its HAT activity and/or by bridging active interaction between STAT6 and general transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Results in this study demonstrated that HDAC inhibitor TSA upregulated the expression of miR-101b and miR-26b in LPS-treated macrophages from the aged mice, but not from the young mice, suggesting that HDAC suppresses the expression of miR-101b and miR-26b in the macrophages of aged mice. Deng et al (2004) reported that LPS could increase p300 HAT binding to COX-2 promoter and subsequently upregulate COX-2 protein levels. In the present study, we firstly observed that TSA strongly reduced the expression of COX-2 protein in response to LPS stimulation in aged mouse macrophages.…”
Section: Tsa Suppresses Cox-2 Protein Expression By Upregulation Of Mmentioning
confidence: 99%
“…Analysis of COX-2 Promoter Activity. A promoter region of human COX-2 gene (−891 to +9) was constructed into luciferase reporter vector pGL3 as previously described (38). A detailed procedure is provided in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…The negative control sequence was 5'-UUC UCCGA A CGU GUC ACG UTT-3'. Cells were transfected with siRNA duplexes using Lipofectamine 2000 (Invitrogen) as previously described (38). The procedure is described in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%